A study on the awareness, attitudes and performance of teachers towards the organ donation during 2016-2017 - Mozhgan Mohammadpour; Ali Mohammadpour; Hosein Ajam-Zibad; Samaneh Najafi (Tehran University of Medical Sciences, 2018)
Background & Aim: providing an organ for donation is a fundamental issue, but the rate of donation in our country is not favorable. Having awareness, attitude and performance to the organ donation are essential for groups that affected public opinion. The information and knowledge teachers provide for students is the basis for the future attitude toward this topic. The aim of the present study was to examine the awareness, attitude, and performance of teachers toward organ donation. Materials and Methods: the research method was descriptive and cross-sectional. The sample of research were 340 teachers in Torbat-e Heidariyeh in 1396. Data collection instruments were researcher-made valid and reliable questionnaire which was used to assess demographic information, awareness, attitude and performance of individuals. Data were analyzed by using Spss 22 software, descriptive and analytical statistics. Results: the mean age of participants were 41/7±8/01and about 68/2 % of them had bachelor's degree. 91/2 % of them did not participate in the course related to the donation. The mean score of awareness, attitude, and participation were 12/66±2/92, 98/08±10/39and 2/78±1/57 respectively. There were significant relationships among awareness, attitude and teachers performance about organ donation with age, teaching experience, education levels, teaching levels, disciplines of teaching and experience of participation in the course (P <0.05), but there was no significant relationship with gender. Conclusion: despite the average awareness and favorable attitude towards organ donation, unfortunately, there was no proper performance toward donation. This qualification was related to demographic features of individuals. These finding suggesting a focus on educational and advertising program for teachers that play an important role in changing the existing opinion to organ donation in students, families, and society.